2008
DOI: 10.1002/prot.21959
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of UDP‐N‐acetylglucosamine enolpyruvyl transferase fromHaemophilus influenzaein complex with UDP‐N‐acetylglucosamine and fosfomycin

Abstract: Transfusion‐dependency is associated with poor prognosis in patients with MDS although the causal link for such association is disputed. This study tests thee hypotheses on the association between transfusion burden and prognosis in the MDS: (1) the cumulative transfusion burden is a confounder merely reflecting the time elapsed from diagnosis; (2) it is a surrogate for higher transfusion intensity, which would reflect a more severe disease; and (3) it is the total amount of transfused RBC units that influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…Inspection of the crystal structure of E. coli MurA complexed with fosfomycin does not suggest an obvious role for Asp-369 and Leu-370 in the protein-inhibitor interaction [24]. However, these amino acids are well conserved among various bacterial species, including Enterobacter cloacae, Haemophilus influenzae, Bacillus subtilis and Staphylococcus aureus [25], suggesting that they are important for the interaction with the substrate phosphoenolpyruvate and its structural analogue fosfomycin. In some natural fosfomycin-resistant organisms, such as Mycobacterium tuberculosis and Chlamydia trachomatis, Asp-115 at the active site of MurA has been identified as conferring resistance [26,27].…”
Section: Discussionmentioning
confidence: 92%
“…Inspection of the crystal structure of E. coli MurA complexed with fosfomycin does not suggest an obvious role for Asp-369 and Leu-370 in the protein-inhibitor interaction [24]. However, these amino acids are well conserved among various bacterial species, including Enterobacter cloacae, Haemophilus influenzae, Bacillus subtilis and Staphylococcus aureus [25], suggesting that they are important for the interaction with the substrate phosphoenolpyruvate and its structural analogue fosfomycin. In some natural fosfomycin-resistant organisms, such as Mycobacterium tuberculosis and Chlamydia trachomatis, Asp-115 at the active site of MurA has been identified as conferring resistance [26,27].…”
Section: Discussionmentioning
confidence: 92%
“…The three dimensional model (Figure 10C) was 100% simulated at >90% confidence by using three different bacterial MurA as structure templates viz ., E. coli (PDB: 1UAE) [44], H. influenzae (PDB: 2RL1) [45] and Enterobacter cloacae (PDB: 1EJD) [46] selected by sequence similarity with w Bm-MurA. The Ramachandran plot for a refined w Bm-MurA homology model revealed that 91.9% residues were in the most favored region, 5.5% in the additional allowed region, 2.1% in the generously allowed region and 0.5% in the disallowed region (Figure S2A), thus making the model geometrically acceptable.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting covalent adduct blocks catalysis, thus reducing the pool of peptidoglycan precursors. Crystal structures of multiple MurA–ligand complexes suggest that the mechanism of inhibition involves flexibility of a loop that lies in close proximity to the active site Cys residue, which can “trap” fosfomycin within the active site cleft …”
Section: Resistance To Antibiotics That Target Cytoplasmic Stepsmentioning
confidence: 99%